A Forum on Emerging Technologies. (August 2022) - Litwin, Adam Seth; Hammerling, Jessie HF; Carré, Françoise; Tilly, Chris; Benner, Chris; Mason, Sarah; Viscelli, Steve; Gutelius, Beth; Theodore, Nik
As part of ILR Review 's new special series "Novel Technologies at Work, " this article introduces a forum composed of five industry studies that examine the drivers and impact of recent and impending technological change. Each of the studies, condensed from longer reports published over the past two years, relies on interviews with sectoral actors and other primary data to determine the relevant technologies confronting workers and managers and the sorts of strategies and policies that will mediate their effects.